Sosialisasi Dan Pembuatan NIB Bagi UMKM Di Desa Karangan, Bareng, Jombang - Anugrah Bayu Santoso; Nanik Hariyana (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
The lack of knowledge from MSME actors in Karangan Village regarding business legality and NIB means that many MSME actors in Karangan Village do not have an NIB. Therefore, to help UMKM actors in Karangan Village who do not have knowledge about NIB and how to make it, a socialization and assistance program for making NIB was carried out for MSME actors in Karangan Village. This activity aims to provide knowledge to MSMEs regarding the benefits of creating a Business Identification Number and strengthen business legality for MSME actors in Karangan Village. Activities are carried out using survey and observation methods, interviews, discussions, and application. The results obtained from this activity are socialization to partner MSME actors regarding business legality, namely NIB.